(untitled) (Altre Modernità, 2022)
Since the outbreak of the coronavirus pandemic, the Chinese political leadership has devoted substantial efforts to shape, through media and institutional discourses, a specific narrative of its response to the crisis, framing it as a fight in which the Chinese people, under the leadership of Xi Jinping and the Chinese Communist Party, promptly came together to defeat the virus. The present paper examines this dominant narrative focusing on the Chinese language section on the fight against COVID-19 of the multilingual online platform China Keywords, a project run by State and Party-affiliated institutions. Drawing on the theoretical background and analytical tools from Critical Discourse Studies, the paper provides an analysis of the discursive representation of social actors constructed by this tool. The analysis shows how different discursive strategies employed to represent specific social actors contribute to reinforce the constitutive elements of the Chinese leadership’s dominant narrative of the events of early 2020. Moreover, the paper argues that the section of China Keywords on the topic should be understood as one of the products of the multifaceted institutional efforts to “tell China’s Covid-19 story well,” both domestically and internationally.